(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2011)
Helminthes infections are chronic illnesses in human beings and in cattle. Pherithema posthuma a helminthes is commonly known as earth-worms. Although the use of alternate drugs has been as a remedial measure against the resistant strains of helminth parasites, and as a means of reducing the cost of controlling helminthic diseases. Catharanthus roseus is a medicinally valuable plant and possess various pharmacological properties. Catharanthus roseus has been traditionally used as an anthelminthic agent. To justify the ethnomedical claims, the anthelminthic property of Catharanthus roseus was evaluated using Pherithema posthuma as an experimental model. Piperazine citrate was used as the standard reference. Among the various concentrations tested, ethanol extract at 200 mg/ml showed efficient paralysis effect (6.67 min) than other treated groups, whereas ethanol extract 250 mg/ml showed significant anthelminthic activity with death time of 46.33 min. Standard drug at 50 mg/ml showed paralysis at 31.33 min and death time was 40.67 min. This investigation revealed that ethanol extract of Catharanthus roseus showed significant anthelminthic activity against Pheretima posthuma. Ethanol extract also proved to be efficient than the standard drug. This investigation supported the ethnomedical claims of Catharanthus roseus as an anthelminthic plant.